A Chinese Ghost Story: A Hong Kong comedy film's cult following in Mainland China. Issue 2 (4th May 2018) - Wang, Hongjian
ABSTRACT: This article aims to explain how and why a Hong Kong comedy film, A Chinese Ghost Story (1987), which did not have access to the movie theatres in mainland China, has generated a phenomenal cult following there. It also endeavours to understand the relationship between comedy film and cult film. It approaches these questions by analysing the comic dialectics of and the audience responses to the film. Sorting through fans' reviews of the film posted on Douban.com, one of the leading interest-based social network sites in mainland China, reveals that it is members of the 'post-80s' – the generation born in the 1980s – who constitute the core of the film's cult following, and that they take the film very seriously, deriving from it idealism, rebellion, nostalgia, and social criticism. Informed by theories on comedy film and cult film, I find that the film is comic because of its half-seriousness, expressed in a katastasis of concerns, and that this half-seriousness is also the foundation of its cult following. Comedy film and cult film seem to be natural allies as both work with a sense of detachment and both are at once transgressive and recuperative.